2013
DOI: 10.1088/0960-1317/23/3/035001
|View full text |Cite
|
Sign up to set email alerts
|

A capacitive power sensor based on the MEMS cantilever beam fabricated by GaAs MMIC technology

Abstract: In this paper, a novel capacitive power sensor based on the microelectromechanical systems (MEMS) cantilever beam at 8-12 GHz is proposed, fabricated and tested. The presented design can not only realize a cantilever beam instead of the conventional fixed-fixed beam, but also provide fine compatibility with the GaAs monolithic microwave integrated circuit (MMIC) process. When the displacement of the cantilever beam is very small compared with the initial height of the air gap, the capacitance change between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The authors found that the grounded gold membrane would reach saturation when input power is >600 mW. For now, the reported maximum input power of the linear region is no more than 400 mW [6,9,10] (see Table 1). It is discovered that the beams they used prefer regular shapes, which is considered to be a potential factor for the nonlinearity.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The authors found that the grounded gold membrane would reach saturation when input power is >600 mW. For now, the reported maximum input power of the linear region is no more than 400 mW [6,9,10] (see Table 1). It is discovered that the beams they used prefer regular shapes, which is considered to be a potential factor for the nonlinearity.…”
Section: Introductionmentioning
confidence: 88%
“…They showed good microwave performances but the power capability was not mentioned. Therefore, Yi and Liao [9] presented a cantilever beam power sensor at X-band. The authors discussed the cantilever displacement under different power levels.…”
Section: Introductionmentioning
confidence: 99%
“…While we emphasize that very high modulation frequency is not required for the envisioned on chip optical switching and reconfiguration applications, the mechanical resonance frequency scales as ~t/L 2 and is able to increase up to 100 MHz with fixed beam thickness and drive voltage. Furthermore, non-plasmonic nanomechanical cantilever devices of similar dimensions have been made operating up to 1GHz with careful material choice, 30,31 and such a fast, yet ultrasmall modulator can potentially operate at low voltage with the use of piezoelectric actuation. [32][33][34] Considering the negligible power dissipation of its electrostatic-drive, actuation voltages at the level of the smallest high speed transistors, its length scale and feature size at the level of CMOS metallization layers, its broadband optical operation and its reasonable speed, we argue 9 that a GPPM can play a unique and important role as a building block for optoelectronic integration.…”
mentioning
confidence: 99%
“…Introduction: Radio frequency (RF) microelectromechanical systems (RF MEMS) power sensors have become important tools for signal power measurements. Recently, capacitive RF MEMS power sensors have been widely studied owing to their small temperature influence and high dynamic range [1][2][3][4], compared with thermoelectric power sensors [5][6][7]. However, these capacitive sensors must be grounded anchors of MEMS beam as a capacitor's electrode so that it is impossible to adopt a balanced-bridge impedance technique for an accurate measurement of capacitance change.…”
mentioning
confidence: 99%
“…Fernandez et al [2] and Dittmer et al [8] have reported two capacitive MEMS power sensors fabricated on the glass substrate, where anchors of the MEMS beam are not connected with ground lines, but they are not compatible with the traditional GaAs or Si process. Furthermore, operation frequencies of these capacitive sensors are up to 1 GHz [8], up to 4 GHz [1,2] and 8-12 GHz [3,4].…”
mentioning
confidence: 99%